2015
DOI: 10.1002/ejlt.201500112
|View full text |Cite
|
Sign up to set email alerts
|

Micronized natural talc with a low particle size and a high carbonate rate is more effective at breaking down oil‐in‐water emulsion

Abstract: Micronized natural talc (MNT) has demonstrated to be very useful to break down emulsions formed during the virgin olive oil extraction process, improving the oil yield. This study was aimed to obtain more insights into the mechanisms of MNT to break down oil‐in‐water emulsions. For this purpose, laboratory scale experiments were performed in order to evaluate the effect of different pectin concentrations (0.5, 1, 1.5, and 2%), used as an emulsifier agent, on the behavior of an oil‐in‐water interface. Afterward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…It was proposed that the action of talc is based on the adsorption of pectins and of pectic‐protein electrostatic complexes on its surface, which act as emulsifiers in the olive paste. This adsorption was also shown for pectins in a model system (Aguilera et al, ; Sadkaoui et al, , ). Crucial variables affecting oil extraction yield except talc dosage are particle size and calcium carbonate rate, as suggested in laboratory experiments (Moya et al, ; Sadkaoui et al, ).…”
Section: Malaxationsupporting
confidence: 61%
See 3 more Smart Citations
“…It was proposed that the action of talc is based on the adsorption of pectins and of pectic‐protein electrostatic complexes on its surface, which act as emulsifiers in the olive paste. This adsorption was also shown for pectins in a model system (Aguilera et al, ; Sadkaoui et al, , ). Crucial variables affecting oil extraction yield except talc dosage are particle size and calcium carbonate rate, as suggested in laboratory experiments (Moya et al, ; Sadkaoui et al, ).…”
Section: Malaxationsupporting
confidence: 61%
“…The addition of coadjuvants during malaxation is recommended to help break down oil/water emulsions and consequently make oil extraction easier and more efficient (Aguilera et al, ; Ben Brahim et al, ; Ben‐David et al, ; Canamasas and Ravetti, ; Caponio et al, , ; Carrapiso et al, ; Cruz et al, ; De Faveri et al, ; Espinola et al, , ; Majetić Germek et al, ; Moya et al, ; Pérez et al, ; Sadkaoui et al, , , b; Squeo et al, ; Tamborrino et al, ). The most common coadjuvants examined in the literature are talc, calcium carbonate, salt, and enzymes.…”
Section: Malaxationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sadkaoui et al studied the effect of the physicochemical properties of MNT on the emulsifying activity of pectins in an oil‐in‐water system (pectins may be considered mainly responsible for oil emulsification during the processing of difficult olive pastes) and showed that both the dosage and type of MNT significantly affected the breakdown of oil‐in‐water emulsions. The authors highlighted that the MNT dose was the main factor explaining the variability of the emulsifying activity values.…”
Section: Resultsmentioning
confidence: 99%